Production of Antimicrobial Films by Incorporation of Partially Purified Lysozyme Into Biodegradable Films of Crude Exopolysaccharides Obtained From Aureobasidium Pullulans Fermentation - Kandemir, Nilay; Yemenicioğlu, Ahmet; Yemenicioğlu, Ahmet; Mecitoğlu, Çiğdem; Elmacı, Zehra Seda; Arslanoğlu, Alper; Arslanoğlu, Alper; Göksungur, Mehmet Yekta; Baysal, Taner (University of Zagreb, 2005)
Antimicrobial films were produced by incorporating partially purified lysozyme into films of crude exopolysaccharides (59% pullulan) obtained from Aureobasidium pullulans fermentation. After film making, the films containing lysozyme at 100, 260, 520 and 780 μg/cm2 showed 23 to 70% of their expected enzyme activities. The highest recovery of enzyme activity (65-70%) after the film making was obtained in films prepared by incorporating lysozyme at 260 μg/cm2 (1409 U/cm2). The incorporation of disodium EDTA·2H2O and sucrose did not affect the initial lysozyme activity of the films significantly. With or without the presence of disodium EDTA·2H2O at 52 or 520 μg/cm2, lysozyme activity showed sufficient stability in the films during 21 days of cold storage. However, the presence of sucrose at 10 mg/cm2 in the films caused the destabilization of part of enzyme activity (almost 35%) at the end of storage. The combinational incorporation of lysozyme at 780 μg/cm 2 (4227 U/cm2) and disodium EDTA·2H2O at 520 μg/cm2 gave antimicrobial films effective on Escherichia coli. However, in the studied lysozyme concentration range the films did not show any antimicrobial activity against Lactobacillus plantarum. This study clearly showed that the partially purified lysozyme and crude exopolysaccharides from Aureobasidium pullulans may be used to obtain antimicrobial films to increase the safety of foods.
Keywords: Antimicrobial films; Aureobasidium pullulans; Exopolysaccharides; Lysozyme; Pullulan